Effectiveness of Fluroxypyr-Based Herbicides for Efficient Weed Management in Sweet Corn (Zea Mays Saccharata) - Muminovna, Turdieva Nilufar; Sayfiddinovna, Shernazarova Nargiza; Esirgapovich, Narmatov Sardor; Musurmonovna, Abdumuminova Muqaddam (American Journal of Biodiversity, 2025)
The aim of this study was to evaluate the effectiveness of various herbicides and weed control in sweet corn crops in the Yashil Ziroat farmer's field in Kibray district of Tashkent region of the Republic of Uzbekistan in 2025. The study developed methods for monitoring weeds and determining optimal doses of herbicides, as well as recommendations for their effective use.